Medical tourism in South East Asia: Science mapping of present and future trends - Muhammad Ashraf, Fauzi; Norhana, Mohd Aripin; Nur Sofia Nabila, Alimin; Ting, Irene Wei Kiong; Wider, Walton; Siti Sarah, Maidin; Zainul-Abideen, Ahmed Yousif Abbas (Emerald Publishing, 2024)
This study evaluates the knowledge structure of medical tourism within the geographical context of South East Asia. This region is one of the growing economic powerhouses in the world, and tourism activities have contributed a lot to its advancement. Design/methodology/approach: Applying a science mapping technique using bibliometric analysis, the current and emerging themes and future trends are analyzed using bibliographic coupling and co-word analysis. Findings: Findings show that current trends produced four themes: Fundamentals of medical tourism in Southeast Asia, determinants of tourist medical tourism visits, quality of medical and health service in Southeast Asia and impact of medical tourism on national economic growth. The future trends also produced four themes related to navigating excellence in medical tourism, medical tourism and economic growth, service quality in medical tourism services and accredited destinations in the globalized era of medical tourism. Research limitations/implications: This study is relevant to all stakeholders, operators and local communities in Southeast Asia tourism destinations to provide the best medical tourism with the best quality service and technologies. Originality/value: This study fills the gap by performing a bibliometric approach to reviewing medical tourism in Southeast Asia using a science mapping technique. Crucial themes are produced through topological and temporal streams that provide critical insight for future developments in medical tourism in the region.